PEMANFAATAN MEDIA WHATSAP DAN SELF REQULATED TERHADAP HASIL BELAJAR AKIDAH AKHLAK DI MTs-DDI KABUPATEN BULUKUMBA - Muh Yusuf T; Safei; Mayani (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research aims to determine the effect of using WhatsApp media on Akidah Akhlak learning outcomes for class VII students at Mts. DDI Baburridha Sawere, Bontoraja Village, Bulukumba Regency. This type of research is retrospective. The research population consisted of all class VII MTS DDI students, with a total sample of 40 individuals taken from the population. The results of this research show that the variables of the use of WhatsApp and self-help media have a combined influence on student learning outcomes. This research implies that students must be able to use WhatsApp media effectively, independent students must be implemented appropriately, that Madrasahs can use learning using WhatsApp media as input in efforts to improve the quality of education, and that innovation in active learning is suitable for improving learning outcomes. The morals of the Aqidah are correct